Optimization of aloe vera‐sodium alginate composite coating using L16 orthogonal design for extension of shelf life of mushroom - Sumaiya Fatima; Vivek Kumar; Geeta Bhadauria (Future Postharvest and Food)
Abstract White button mushrooms are highly nutritive, rich in various macro and micro nutrients, however, have a short shelf life with weight loss (WL), enzymatic browning, and loss in firmness as the major quality defects. The present study was carried out to investigate the effect of aloe vera‐sodium alginate (AV‐SA) composite coating on the quality attributes of mushroom. The development of coating formulations containing 2% sodium alginate along with varying concentration of aloe vera gel 20%–80% and storage time 4–16 days was planned using a 2‐factor 4‐level orthogonal array (L16) design of Taguchi technique. The influence of both the process parameters on the WL, total soluble solids (TSS), respiration rate (RR), browning index (BI), firmness, electrolyte leakage rate (EL), malondialdehyde (MDA), ascorbic acid (AA), total phenolic content (TPC), enzymes activity (polyphenol oxidase and peroxidase), and yeast and mold count (YMC) were evaluated and the optimized level of parameters was determined on the basis of the highest S/N ratios of the responses. The results indicated that 60% AV‐SA composite coating could extend the shelf life of white button mushrooms for up to 8 days with retarded loss in weight, firmness, AA, and TPC and reduced increase in TSS, BI, EL, MDA with controlled enzymatic activity, RR, and YMC.